Generative Artificial Intelligence As A Catalyst For Behavior Driven Development And Educational Software Quality Assurance In The Era Of Intelligent Automation - Adrian Markus Feldmann (Academic Reseach Library for International Journal of Computer Science & Information System, 2026)
The rapid expansion of generative artificial intelligence has transformed both educational technology and software engineering by redefining how knowledge, behavior, and automated systems interact. In particular, the convergence of behavior driven development and generative artificial intelligence has emerged as a pivotal area of scholarly and industrial attention, enabling intelligent test automation, enhanced software reliability, and pedagogically informed system validation. This study offers a comprehensive and theoretically grounded investigation into the role of generative artificial intelligence in automating behavior driven development workflows, with special emphasis on educational software systems that increasingly depend on adaptive, data driven, and learner centered architectures. Anchored in the foundational contribution of Tiwari (2025), which demonstrates how generative artificial intelligence can enhance efficiency and accuracy in behavior driven test automation, this research situates that insight within a broader interdisciplinary framework drawing from explainable artificial intelligence, transformer based language modeling, educational artificial intelligence ethics, and software quality theory. The article advances the argument that generative artificial intelligence does not merely optimize existing test automation pipelines, but fundamentally reshapes the epistemological assumptions underlying how software behavior is specified, verified, and validated. Traditional behavior driven development relies on human authored scenarios that attempt to translate stakeholder intent into executable tests, yet these human produced artifacts are often incomplete, ambiguous, and misaligned with evolving system behaviors. By contrast, generative artificial intelligence systems trained on vast corpora of software documentation, natural language specifications, and historical testing artifacts possess the capacity to infer latent behavioral patterns and generate contextually relevant test cases that continuously adapt to system evolution. Drawing upon contemporary research in natural language processing and contextual embeddings, this study argues that such systems operate as cognitive mediators between human intent and machine execution, effectively operationalizing stakeholder expectations in a dynamic and scalable manner (Akbik et al., 2018; Al Sabahi et al., 2018). Beyond software engineering, the implications of this transformation are particularly profound in educational environments, where artificial intelligence driven platforms increasingly mediate assessment, instruction, and feedback. Educational software must adhere to ethical, pedagogical, and reliability standards that exceed those of conventional enterprise systems, making robust behavior driven testing not merely a technical requirement but a moral and social imperative (Holmes et al., 2022; Gonzalez Calatayud et al., 2021). Generative artificial intelligence offers the potential to align automated testing with educational values by encoding fairness, transparency, and learner centeredness directly into executable behavioral specifications. This article therefore conceptualizes generative behavior driven development as a socio technical system in which algorithms, educators, learners, and developers co construct the meaning of software correctness. Methodologically, the study adopts a qualitative analytical framework grounded in comparative literature synthesis, theoretical modeling, and interpretive reasoning. Rather than relying on numerical simulation or experimental metrics, the research integrates diverse strands of scholarship on generative adversarial networks, explainable artificial intelligence, educational artificial intelligence ethics, and intelligent tutoring systems to develop a cohesive explanatory model of how generative artificial intelligence transforms behavior driven development. The results articulate a multi layer interpretive model in which generative artificial intelligence enhances test coverage, semantic fidelity, and adaptive responsiveness while simultaneously introducing new epistemic risks related to bias, hallucination, and over automation. The discussion critically evaluates these tradeoffs, situating generative behavior driven development within ongoing debates about the role of artificial intelligence in education, the governance of algorithmic systems, and the future of software engineering professionalism. Ultimately, this study concludes that generative artificial intelligence represents not merely a technical tool but a paradigm shift that compels a rethinking of how behavior, quality, and trust are constructed in digital educational ecosystems.